Post- independence Shona poetry, the quest and struggle for total liberation - Tembo, Charles (Unisa, 2022)
This study pursues the quest and struggle for total liberation in post-ndependence Shona poetry. The study also relies on views of key respondents obtained through interviews and questionnaires. Couched and guided by Afrocentricity and Africana womanism, the study elucidates the politico-economic and socio-cultural factors that militate against Africa’s total liberation in general as well as women’s liberation, respectively. Simultaneously, critical judgments are passed on the extent to which poets immerse their art in African existential philosophy. The study is energized by the idea that pursuing the quest for authentic liberation provides a lens through which one can understand threats to Africa’s true liberation. It observes that poets and key informants largely attribute ersartz independence to internal problems. The researcher holds that it is problematic to hold a domesticated vision of the African condition to the extent that poets and other literary workers need to widen their canvas beyond fighting internal oppression and internationalise the struggle. The researcher argues that it is myopic and self-defeating to protest against Africa itself without giving adequate attention to the incapacitating hegemonic world system. Therefore, the poetry is lacking on its critique on domination. The centerpiece of the thesis is that in order to be purposeful and functional, poets need to grapple with both endogenous and exogenous factors that obstruct the march towards genuine liberation. The study also observes that in some instances poets produce cheap literature which is marked by a narrow and moralistic approach and this is attributable to the fact that poets lack a scientific vision in understanding reality. Concerning women’s authentic liberation, the commonly identified obstacles to women’s freedom are the male counterpart, self-depreciation, lack of education and culture. The study observes that women poets in Ngatisimuke (1994) and key respondents seem to approach gender relations from a feminist perspective and hence fail to situate women’s condition in the context of the history and culture that shape African gender relations. Women poets in Ngatisimuke fall short of internationalising their struggle in concert with the male counterpart such that their poetry degenerates into sponsored and misguided activism.